The effectiveness of long-term course of Sterimar Mn nasal spray for treatment of the recurrence rates of acute allergic rhinitis in patients with chronic allergic rhinitis - Grasso M; de Vincentiis M; Agolli G; Cilurzo F; Grasso R (Dove Medical Press, 2018)
Michele Grasso,1 Marco de Vincentiis,1 Griselda Agolli,1 Francesco Cilurzo,2 Raffaele Grasso2 1ENT Department, Head and Neck Surgery, University “Sapienza”, Rome, Italy; 2ENT Department, Head and Neck Surgery, Lamezia Terme Hospital, Calabria, Italy Background: The “cost of illness” of the acute allergic rhinitis (AR) episodes in patients with chronic AR is very high in terms of therapy and quality of life. AR represents a worldwide health problem; despite the fact that many standardized treatments have been proposed and used, the recurrence rate of acute rhinitis episodes in springtime is always higher.Materials and methods: Sixty consecutive patients (13 F and 17 M in group A, 15 F and 15 M in group B; p=0.60) with chronic AR were enrolled in this prospective, controlled clinical trial. Thirty patients were treated daily for the same 5 months of the following year (2013) with isotonic seawater nasal spray enriched with manganese (Sterimar Mn; 4 puffs/day), whereas 30 patients received only the standard care and were used as control group.Results: A 5 months course treatment with the nasal Sterimar Mn was able to decrease, significantly (p<0.001), the number of episodes of acute AR (6.33 episodes in the group of treated patients versus 9.33 episodes in control group). Also, the 5 months quality of life reduced over time (Visual Analogue Scale 5th month 9.90 in treated group versus Visual Analogue Scale 5th month 8.72 in control group: p<0.001) without the typical adverse effects of the AR standard care therapy.Conclusion: This study shows the effectiveness of the use of Sterimar Mn for a 5 months therapy in terms of reduction of the number of episodes of acute AR and effectiveness of intrasubject improvement of Visual Analog Scale (quality of life). Keywords: chronic allergic rhinitis, acute allergic rhinitis, prevention, nasal detersion, Sterimar Mn